2014
DOI: 10.1590/1983-1447.2014.02.45178
|View full text |Cite
|
Sign up to set email alerts
|

Skin tear treatment and prevention by nurses: an integrative literature review

Abstract: The objective of the present study was to identify scientifi c evidence in the literature regarding management and prevention of skin tears by nurses over the last ten years. This is an integrative review of articles found in the LILACS, SciELO, BDENF, MEDLINE, Scopus, ScienceDirect and PubMed databases, identifi ed with the Portuguese, English and Spanish descriptors for "skin, " "friction, " or with the keyword "skin tears". After inclusion and exclusion criteria were applied, fi fteen texts were selected. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
(29 reference statements)
0
12
0
6
Order By: Relevance
“…In order to reach the proposed objective, a study of integrative revision of the literature was developed, aiming at integrating the data abstracted from different studies which, in turn, adopted different methodologies, which enables the search, the critical evaluation and the synthesis of the available evidences on a specific theme. Six steps inherent to this method were followed; which were: the establishment of the matter of research, the search in the literature, the categorization of the studies, the evaluation of the studies included in the revision, data interpretation of the results and the presentation of the revision (6)(7) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reach the proposed objective, a study of integrative revision of the literature was developed, aiming at integrating the data abstracted from different studies which, in turn, adopted different methodologies, which enables the search, the critical evaluation and the synthesis of the available evidences on a specific theme. Six steps inherent to this method were followed; which were: the establishment of the matter of research, the search in the literature, the categorization of the studies, the evaluation of the studies included in the revision, data interpretation of the results and the presentation of the revision (6)(7) .…”
Section: Methodsmentioning
confidence: 99%
“…Found Selected Figure 4. It is necessary to highlight the low level of evidence (6)(7) of most part of the studies identified, which in most cases, obtained a punctuation around 4 and 5 points. This result shows the still modest character, in quantitative terms, of the controlled and experimental clinical studies on Fournier's gangrene published in Brazil in the last twenty years.…”
Section: Data Basismentioning
confidence: 99%
“…Vale acrescentar que esta técnica tem sido apontada como possibilidade ao tratamento da LP, conforme descrito pelos autores (29) , porém, parece não ser eficaz quando aplicada isoladamente. Em se tratando dos cuidados das LF, apontado por discreta parcela dos participantes, os cuidados mencionados coadunam ao proposto pela literatura (30) , que sugere a terapia tópica enquanto cobertura, desde que haja retalho de pele viável, passível de realinhamento.…”
Section: Introdução Métodounclassified
“…No que diz respeito à retirada atraumática do adesivo, esta medida tem sido mais associada à prevenção de LF, do que ao tratamento da lesão. Porém, ao deparar-se com a necessidade deste uso, o Enfermeiro deve dar preferência a fitas de baixa capacidade adesiva (30) . Chama atenção o fato de uma das entrevistadas mencionar que a padronização do cuidado deve ser evitada, uma vez que a condução do tratamento está diretamente relacionada às características da lesão.…”
Section: Introdução Métodounclassified
See 1 more Smart Citation